Penyuluhan Pemasaran dan Pengemasan Ikan Melalui Kargo Udara Bagi Pedagang Sentra Ikan Hias Kabupaten Bogor - Iswahyu Pranawukir (Universitas Prof. Dr. Moestopo (Beragama), 2021)
The ornamental fish market center in the village of Waru Pasar Parung, Bogor Regency, has tremendous potential in supporting the life and economy of its people. While other businesses in this pandemic era are sluggish, the ornamental fish trading business has actually increased, both in face-to-face as well as online transactions. Therefore, mentoring and training to improve understanding of business strategies and promotion of ornamental fish marketing is very important. Mentoring aims to generate creative and innovative entrepreneurial values as well as the search for solutions in facing the challenges of the COVID-19 pandemic. The main goal is to increase sales profits. Problem solving methods are carried out through marketing mentoring and training through ornamental fish business promotion activities, done through questionnaires in Google form format.Mentoring Information is intended to open up their business communication insights and online marketing promotion strategies in the ornamental fish business. During the Mentoring activities for ornamental fish traders in the Parung center, it is found that their business activities were still focused on price, product and place strategies concentrated only within the Parung ornamental fish center. Their promotion strategy is still wide open to grow due to their minimal insight and knowledge in packaging ornamental fish through air cargo. For the traders, the online ornamental fish promotion strategy seems has not been fully implemented and the actual promotion has not been fully understood.